2010
DOI: 10.1038/nmeth.1528
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and design of RNA sequencing experiments for identifying isoform regulation

Abstract: Through alternative splicing, most human genes express multiple isoforms that often differ in function. To infer isoform regulation from high-throughput sequencing of cDNA fragments (RNA-seq), we developed the mixture-of-isoforms (MISO) model, a statistical model that estimates expression of alternatively spliced exons and isoforms and assesses confidence in these estimates. Incorporation of mRNA fragment length distribution in paired-end RNA-seq greatly improved estimation of alternative-splicing levels. MISO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
1,438
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,264 publications
(1,465 citation statements)
references
References 35 publications
25
1,438
0
2
Order By: Relevance
“…This protein tends to form a heterodimer with hnRNP F and shows preference for G-rich tracts of RNA. 2,[6][7][8] It has also been shown that hnRNP H1 interacts with the DGCR8 complex and facilitates microRNA processing in HeLa cells. 9 The impact of hnRNP H1 binding on alternative splicing has been associated with several diseases, such as cystic fibrosis, 10 congenital myasthemic syndrome, 11 and amyotrophic lateral sclerosis (ALS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This protein tends to form a heterodimer with hnRNP F and shows preference for G-rich tracts of RNA. 2,[6][7][8] It has also been shown that hnRNP H1 interacts with the DGCR8 complex and facilitates microRNA processing in HeLa cells. 9 The impact of hnRNP H1 binding on alternative splicing has been associated with several diseases, such as cystic fibrosis, 10 congenital myasthemic syndrome, 11 and amyotrophic lateral sclerosis (ALS).…”
Section: Introductionmentioning
confidence: 99%
“…18 In addition to these targeted analyses, genome-wide studies have revealed hnRNP H1s role, in conjunction with hnRNP F, in promoting both exon inclusion and skipping. 8 Other recent studies have linked hnRNP H1 to alternative cleavage and polyadenylation, 6 and established the cooperative roles of the hnRNP proteins in the regulation of splicing. 2 By employing a combined strategy with 4 different high-throughput approaches, we were able to provide a more refined and accurate picture for hnRNP H1 in splicing regulation and extend our understanding of its participation in polyadenylation and mRNA decay.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to microarrays, RNA expression profile has two majorly advantageous features to enable to identify complexity of isoform variability on a single gene to produce various splicing events on transcripts and another nature, allelic specific expression and allelic imbalance resulted from genetic differences in transcriptional rates (Beretta et al, 2014;Bernard et al, 2014;Deng et al, 2011;Hiller et al, 2009;Hiller and Wong, 2013;Howard and Heber, 2010;Hu et al, 2014;Jiang and Wong, 2009;Katz et al, 2010;Kaur et al, 2012;Kimes et al, 2014;Leon-Novelo et al, 2014;Lerch et al, 2012;Li and Jiang, 2012;Ma and Zhang, 2013;Mezlini et al, 2013;Mills et al, 2013;Nariai et al, 2013;Nariai et al, 2014;Ng et al, 2014;Nicolae et al, 2011;Niu et al, 2014;Pandey et al, 2013;Patro et al, 2014;Rehrauer et al, 2013;Safikhani et al, 2013;Shi and Jiang, 2013;Suo et al, 2014;Trapnell et al, 2010;Vardhanabhuti et al, 2013;Wang et al, 2010;Wu et al, 2011b;Yalamanchili et al, 2014;Zhang et al, 2014;Zheng and Chen, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…This normalization allows to focus on splicing patterns rather than on transcript levels. To do so, MISO integrates the number of reads aligning to the alternative exon with the number of junctional reads linking it to neighboring exons, with the numbers of junctional reads excluding it, and with the number of reads in the immediately neighboring exons (Katz et al, 2010). SpliceTrap generates an exon-trio database (all the possible 3 consecutive exons in the annotation), generates two isoforms for each trio (with or without the middle exon) and quantifies the relative abundances of the two isoforms to infer middle exon usage (Wu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%